Analisa Pelayanan Tiket Terhadap Kepuasan Pelanggan Pada PT. Pelayaran Nasional Indonesia (PELNI) Cabang Medan - Sohibudin Sohibudin; Lilis Lilis; Fadiyah Hani Sabila (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
PT. Pelayaran Nasional Indonesia (PELNI) is a company engaged in the field of marine transportation services, namely passenger ships, roro ships, container ships, pioneer ships and so on. Therefore, the importance of "service" to customer satisfaction (passengers) is very influential. Customer service can be defined as all forms of customer service in the form of services and in the form of goods which in principle are the responsibility and are carried out by PT. Pelayaran Nasional Indonesia (PELNI) Medan Branch, in order to fulfill the needs of the community and comply with regulations and laws.